2021
DOI: 10.1111/jvh.13502
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of estimated glomerular filtration rate in human immunodeficiency virus and hepatitis C virus‐coinfected patients receiving sofosbuvir‐based direct‐acting antivirals and antiretroviral therapy

Abstract: The nephrotoxicity of sofosbuvir (SOF) on human immunodeficiency virus and hepatitis C virus (HIV/HCV)‐coinfected patients receiving antiretroviral therapy (ART) remains controversial. We prospectively compared the estimated glomerular filtration rate (eGFR) changes in 167 patients receiving SOF‐based direct‐acting antivirals (DAAs) who also received tenofovir disoproxil fumarate (TFV)‐based (n = 116) and TFV‐free ART (n = 51). The eGFR was assessed by the Chronic Kidney Disease Epidemiology Collaboration (CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(42 reference statements)
3
3
0
Order By: Relevance
“…32 Finally, recent studies that have confirmed the kidney safety of coadministration of SOF with tenofovir-based treatments in HIV/HCV co-infected patients further corroborate this study's findings. 33,34 Our results complement recent findings of clinical trials evaluating LDV/SOF and SOF/VEL in patients with ESRD which concluded these regimens were safe and effective and led to an expanded FDA label for SOF-containing regimens in patients with all levels of kidney function in 2019, 16,17 and data demonstrating that the GS-331007 metabolite is efficiently removed by haemodialysis (53% extraction ratio) resulting in markedly reduced exposure after dialysis. 35 SOF-based treatment, eGFR remained stable after treatment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…32 Finally, recent studies that have confirmed the kidney safety of coadministration of SOF with tenofovir-based treatments in HIV/HCV co-infected patients further corroborate this study's findings. 33,34 Our results complement recent findings of clinical trials evaluating LDV/SOF and SOF/VEL in patients with ESRD which concluded these regimens were safe and effective and led to an expanded FDA label for SOF-containing regimens in patients with all levels of kidney function in 2019, 16,17 and data demonstrating that the GS-331007 metabolite is efficiently removed by haemodialysis (53% extraction ratio) resulting in markedly reduced exposure after dialysis. 35 SOF-based treatment, eGFR remained stable after treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Butt and colleagues examined a large cohort of HCV‐infected Veterans and demographically matched HCV uninfected controls (ERCHIVES) to evaluate the risk of worsening kidney function, defined as a decline in eGFR >30 ml/min/1.73 m 2 from baseline, and found a statistically significantly lower risk associated with SOF‐containing vs non‐SOF‐containing regimens 32 . Finally, recent studies that have confirmed the kidney safety of coadministration of SOF with tenofovir‐based treatments in HIV/HCV co‐infected patients further corroborate this study’s findings 33,34 …”
Section: Discussionsupporting
confidence: 58%
“…36 Our study also confirmed that no patients experienced ≥ grade 2 renal function declines, irrespective of the HIV status or types of DAAs. 24,25 Due to the concomitant use of TAF-based ART for HIV that was also active against HBV, no HBV reactivation or HBV-associated hepatitis was observed in our HBV-coinfected patients.…”
Section: Discussionmentioning
confidence: 91%
“…23,24 In HIV-positive patients, the CD4 count and serum HIV RNA (Cobas Taqman HIV-1 Test v2.0, Roche Diagnostics GmbH, lower limit of quantification [LLOQ]: 20 copies/mL), and information about antiretroviral therapy (ART) were assessed. 25 The stage of hepatic fibrosis was graded by transient elastography (FibroScan, Echosens, Paris, France) with a liver stiffness measurement (LSM) cutoff of ≤7.0 kilopascal (kPa) to be F0 to F1, 7.1 to 9.4 kPa to be F2, 9.5 to 12.3 kPa to be F3, and ≥12.4 kPa to be F4, respectively. 26,27 Patients received SOF/VEL (Epclusa, FDC 400/100 mg per tablet, Gilead Sciences, Carrigtohill, Co. Cork, Ireland) one tablet once daily for 12 weeks or GLE/PIB (Maviret, FDC 100/40 mg per tablet, AbbVie Deutschland GmbH & Co. KG, Germany) three tablets once daily orally for 8 to 12 weeks according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation